(untitled) (Third Sector Social Economic Review, 2025)
In today’s business world, employees who not only perform their tasks but also generate innovation have come to the forefront. This raises an important question: what are the underlying factors that drive innovative work behavior? Based on this premise, the aim of this study is to examine the impact of workplace happiness on innovative work behavior.The study population consists of employees working in public, private, and non-governmental organizations (NGOs) in Istanbul and Ankara. Data were collected through a survey administered to 509 employees using a convenience sampling method. According to the findings, workplace happiness has a positive and significant effect on innovative work behavior. Additionally, the sub-dimensions of workplace happiness—work engagement, job satisfaction, and organizational commitment—were also found to have a positive and significant impact on innovative work behavior. The analysis results indicate that employees’ levels of innovative work behavior and workplace happiness significantly differ depending on the sector in which they work.